CUSTOMER PREFERENCE TOWARD SHAR’I CLOTHING FOR MOSLEM WOMEN IN INDONESIA: THE CASE OF DHAILLY - Ramadhany, Fitri; Aprianingsih, Atik (Journal of Business and Management, 2017)
Abstract. Indonesia is the country that has a big opportunity in Muslim fashion industry. Dhailly as a new player take this opportunity by creating shar’i clothing for moslem women with the handsock function. They want to create the another product variants to compete with another brand but not all their product variant is sold successfully. Therefore, the research about customer preference toward the attributes of shar’i clothing will be needed. The analysis technique in this research is interview with coding analysis and survey with descriptive and conjoint analysis. The results of this research indicates that color, good price, ease of care, quality of product, comfortable, durability, attractiveness, fit, fabric for shar’i dress, fabric for handsock, and design of shar’i clothing are important for Dhailly’s target market. The design attribute will be analyzed with conjoint and the rest of attributes will be analyzed with descriptive analysis. The researcher recommends that Dhailly should create the next design based on the conjoint result, for example, the combination of ribbon on the rear skirt, ban design on the sleeve, plain skirt design, without pattern, and fingerless handsock. Then, Dhailly should pay attention to the highest priority of variable from the descriptive analysis result.  Keywords: Customer preference, Shar’i clothing, Product Attribute, Conjoint Analysis, Moslem women